'Study the past, if you would divine the future': a retrospective on measuring and understanding Quaternary climate change. (February 2015) - MCCARROLL, DANNY
ABSTRACT Research on Quaternary climate change is reviewed from the perspective of the real or potential contribution to improving our ability to predict the climate of the future. For convenience the literature is divided into four timescales: orbital, sub‐Milankovitch, Holocene and the last 2000 years. Four 'challenges' provide a framework for discussion: better understanding of the way the climate system works, better forecasting of the drivers of climate change, improved estimates of climate sensitivity (change in global mean annual temperature per unit increase in forcing) and evaluation of the models used to predict the climate of the future. Although a great deal of progress has been made, it is concluded that there are some aspects of our scientific culture that limit our potential. These include our tradition of storytelling rather than critical hypothesis testing, an over‐emphasis on the role of surface water sinking in the far north Atlantic as a driver of ocean circulation and an attendant under‐emphasis on the critical importance of changes in atmospheric circulation, and a lack of rigour in testing the hypothesis that changes in solar irradiance are an important driver of climate change.